Social Support, Stress, Depression, and Social Conflict : Testing for Main and Moderating Effects with Structural Equations in a Two-Wave Longitudinal Study - Chittilla, Silpa (East Carolina University, 2012)
Previous studies have explored the interaction between supportive and conflictual aspects of social networks in regard to stress and depression. This study proposes to look at how support moderates the effect of social conflict on health, and whether this tendency differs across the four dimensions of support assessed by the Interpersonal Support Evaluation List. A baseline model was created, beta parameter estimates were initially set invariant across levels (i.e., high versus low) of social support, one constraint was released (i.e., the path from social conflict to depression), and the fit of the constrained and unconstrained models was compared using a chi-square difference test. The study hypotheses regarding differential effects of social conflict on depression as a function of differing levels of support were largely supported. The comparison between the high support model and the low support model was significant with the appraisal, belonging, and tangible subscales of the support measure, but not with the self-esteem subscale of the support measure.
Keywords: Psychology; Social Support; Structural equations; Social networks; Social conflict; Stress (Psychology); Depression, Mental